El tema del placer en Platón - Martos-Montiel, Juan Francisco (Sociedad Española de Estudios Clásicos, 1995)
The author sees an evolution of the theory of pleasure in different dialogues of Plato. Martos is aware of the contradictions of this theory in the course of Plato's philosophical development and he says that Aristotle tried to reconcile these contradictions.
Keywords: Placer; Platón